2013
DOI: 10.1557/opl.2013.839
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diisocyanate reactivity and water solubility on the formation and the mechanical properties of gelatin-based networks in water

Abstract: Gelatin can be covalently crosslinked in aqueous solution by application of diisocyanates like L-lysine diisocyanate ethyl ester in order to form hydrogels. Reaction of isocyanate groups with water is however a limiting factor in hydrogel network formation and can strongly influence the outcome of the crosslinking process. Here, diisocyanates with different water solubility and reactivity were applied for the formation of gelatin-based hydrogel networks and the mechanical properties of the hydrogels were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…New peaks around 152.75 appeared, which have been oen assigned as characteristic resonance of polyurea. 65,66 These are strong indication that all -NCO (TDI) were effectively reacted.…”
Section: Ppu Characterization By Nmrmentioning
confidence: 97%
See 2 more Smart Citations
“…New peaks around 152.75 appeared, which have been oen assigned as characteristic resonance of polyurea. 65,66 These are strong indication that all -NCO (TDI) were effectively reacted.…”
Section: Ppu Characterization By Nmrmentioning
confidence: 97%
“…It is well known that TDI has a very limited solubility in water, and the reactivity of its two isocyanate groups is quite different. 65,66 It was questionable that polyurea was effectively formed by dispersing TDI in the binary solvent. To this end, PPU as-prepared was undergone 13 C and 1 H NMR tests.…”
Section: Ppu Characterization By Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…As result, the primary ε-NCO has slightly higher reactivity than the secondary α-NCO. , The combination of the primary ε-NCO and the secondary α-NCO determines the overall reactivity of l -lysine diisocyanates. This was compared to commercial diisocyanates in recent studies, and it is estimated to be equal to the reactivity of HDI (hexamethylene diisocyanate) and higher than that of IPDI, but lower than that of TDI . Less steric hindrance from the planar structure, as well as delocalized electrons into the π-ring system, results in the highest reactivity of aromatic NCO groups such as MDI or TDI, while the lowest reactivity of IPDI comes from high steric hindrance and weak electrophilicity .…”
Section: Biobased Diisocyanates and Polyisocyanatesmentioning
confidence: 99%
“…This was compared to commercial diisocyanates in recent studies, 108 and it is estimated to be equal to the reactivity of HDI (hexamethylene diisocyanate) 109 and higher than that of IPDI, 106 but lower than that of TDI. 110 Less steric hindrance from the planar structure, as well as delocalized electrons into the π-ring system, results in the highest reactivity of aromatic NCO groups such as MDI or TDI, while the lowest reactivity of IPDI comes from high steric hindrance and weak electrophilicity. 111 Studies 106,111 also indicated that the steric hindrance is more effective than the electron withdrawing effect on the final property of the NCO group.…”
Section: Biobased Diisocyanates and Polyisocyanatesmentioning
confidence: 99%